2010
DOI: 10.1007/s11010-010-0412-y
|View full text |Cite
|
Sign up to set email alerts
|

Acid-sensing ion channel 1a mediates acid-induced increases in intracellular calcium in rat articular chondrocytes

Abstract: Acid-sensing ion channels (ASICs) are cationic channels that are activated by extracellular acidification and implicated in pain perception, ischemic stroke, mechanosensation, learning, and memory. It has been shown that ASIC1a is an extracellular pH sensor in the central and peripheral nervous systems, but its physiological and pathological roles in non-neural cells are poorly understood. We demonstrated a novel physiological function of ASIC1a in rat articular chondrocytes. The expression of ASIC1a mRNA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 23 publications
2
43
0
Order By: Relevance
“…Cell isolation and culture Articular chondrocytes were isolated from young adult male Sprague-Dawley rats weighing 160-180 g (n = 24), as described previously [8]. Cartilage from the knee joint was minced into small pieces (about 1 mm 3 ) and digested initially with 0.2% type II collagenase (Sigma Chemical Co.) in phosphate-buffered saline (PBS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell isolation and culture Articular chondrocytes were isolated from young adult male Sprague-Dawley rats weighing 160-180 g (n = 24), as described previously [8]. Cartilage from the knee joint was minced into small pieces (about 1 mm 3 ) and digested initially with 0.2% type II collagenase (Sigma Chemical Co.) in phosphate-buffered saline (PBS).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study also demonstrated that ASICs are involved in acidosis-induced articular chondrocyte injury caused by increased intracellular calcium ([Ca 2? ] i ) [8]. In addition, our previous studies indicated that inhibiting ASICs by amiloride provides protection for the articular cartilage in adjuvant arthritis rats [12].…”
Section: Introductionmentioning
confidence: 98%
“…Blockade of ASIC1a with PcTX1 or specific siRNA inhibited acid-induced osteoclast differentiation and bone resorption via regulating activation of the transcription factor, nuclear factor of activated T cells c1 [10]. Similarly, the ASIC1a-specific blocker PcTX venom attenuated acid-induced articular chondrocyte damage [25]. Furthermore, blocking ASICs markedly decreased calpain and calcineurin expression levels as well as caspase-3/9 activity, and led to recovery of mitochondrial membrane potential via regulation of B-cell lymphoma-2 family gene expression in acid-induced chondrocytes [9,73].…”
Section: Asics and Arthritismentioning
confidence: 99%
“…All the isoforms are expressed in the peripheral nervous system [22], while ASIC1a, ASIC2a and ASIC2b subunits are primarily localized in the central nervous system (CNS) [19,23]. ASIC1a is widely expressed throughout the cerebral cortex, hippocampus, cerebellum, pineal gland, amygdala, dorsal root ganglion, and bone [24][25][26][27]. ASIC1b is almost exclusively expressed in sensory neurons.…”
Section: Structure and Characteristics Of Asicsmentioning
confidence: 99%
“…1c), application of extracellular acid (pH 6.0) significantly increased the [Ca 2? ]i in articular chondrocytes [21]. After acid application, the [Ca 2?…”
Section: Effects Of Amiloride On Asics-mediated Intracellular [Ca 2? ]Imentioning
confidence: 99%